2019
DOI: 10.4236/psych.2019.1014124
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Dissatisfaction in the Choice of the Career of Student’s New Entry to Nutrition

Abstract: The beauty standards currently imposed are affecting the perception of body image (BD) in both men and women, causing many young people to choose the bachelor's degree in nutrition as a way to improve their figure. The aim of the study was to identify the influence of body dissatisfaction in the career choice of new students to the degree in nutrition as compared to those of psychology. The study was quantitative, descriptive, cross-sectional and was conducted with new students entering the bachelor's degree i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…As previously mentioned, some authors argue that the constant contact with food [8,9]; the knowledge related to food, weight control, and body composition [7]; and the belief that a good appearance may be important for professional success [8,9] may lead to an increased prevalence of eating disorders among nutrition students. In addition, some authors suggest that there may be an influence of personal experiences regarding eating and weight control when selecting a nutrition or dietetics course [10][11][12]. Taking these effects into account, there would be a tendency for a higher risk of eating disorders among nutrition/dietetics students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, some authors argue that the constant contact with food [8,9]; the knowledge related to food, weight control, and body composition [7]; and the belief that a good appearance may be important for professional success [8,9] may lead to an increased prevalence of eating disorders among nutrition students. In addition, some authors suggest that there may be an influence of personal experiences regarding eating and weight control when selecting a nutrition or dietetics course [10][11][12]. Taking these effects into account, there would be a tendency for a higher risk of eating disorders among nutrition/dietetics students.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing risk factors for the development of eating disorders, studies have found that constant contact with food [8,9], as well as knowledge on food-related issues, weight control, and body composition [7] and the imposition of strict aesthetic standards on students, with the belief that a good appearance can be important for professional success [8,9], can result in an increased prevalence of eating disorders among nutrition/dietetics students. Also, when analyzing the motivation to attend a nutrition or dietetics course, some authors suggest the possible influence of personal experiences regarding food and weight control [10][11][12]. Indeed, some research has shown that the risk of eating disorders is higher among students in these areas compared to students on other courses [13,14].…”
Section: Introductionmentioning
confidence: 99%